تحقيق التوازن بين الفهم النصي والسياقي: دراسة منهج التفسير للحبيب عمر ابن حفيظ - Muhamad Muhamad (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2024)
This research investigates the exegetical analysis of Surah Muhammad verses 17-19 as articulated by Habib Umar bin Hafidz. The emphasis is placed on its methodological framework and its implications within both global and contemporary paradigms. The methodologies employed encompass documentation analysis and critical analytical strategies. The findings of the inquiry indicate that the interpretation highlights the alignment between textual interpretation and context, thereby facilitating a profound comprehension that remains steadfast amidst evolving circumstances. Additionally, the outcomes of the research reveal how Habib Omar adeptly navigated traditional doctrines and modern ideologies, thereby ensuring that his interpretations are pertinent and comprehensible to a worldwide audience. Noteworthy discoveries encompass the significance of inner purification in Islamic teachings, the societal and spiritual worth of Quranic interpretation, and its impact on contemporary perspectives regarding Islam. These findings emphasize the necessity for a conscientious and contextualized approach to comprehending Islamic doctrine and for establishing a framework that enables Muslims to implement the teachings of the faith in their everyday lives.